El Evangelio de Judas: análisis y controversias - Klein, Fernando (Nómadas. Critical Journal of Social and Juridical Sciences, 2007)
In the beginning of this year the discover of a book that was believed to be lost, the so called Gospel of Judas, impacted the world. Its reading, after of sixteen centuries, allows to obtain a very different vision of Jesus of Nazaret and Judas Iscariot than the one that can be read in the Gospels included in the New Testament, in the Bible. The Gospel belongs to the Gnostic tradition, one of a series of sects that used to compose the initial and fertile universe of Christendom. These texts were hermetical in their language, allegories, and of a very difficult comprehension. The big blame, the big betrayer of the Messiah, was Judas Iscariot who, nowadays, is presented through his Gospel as the best friend of Jesus and the person in charge to initiate His Passion. Let´s remember that in 1868 it was published the very first books that look to redeem him, “Memories of Judas” by Ferdinando Petruccelli della Gattina: in the book Judas had a friendly relationship with Jesus